The State of Low Cost Air Travel in Australia and its Potential for the Future - Verhelst, John E. M. (2009)
This study examines the current state and the market potential of the two Australian low cost airlines, Virgin Blue and Jetstar, using the models and experiences of two successful low cost airlines, Southwest Airlines (USA) and Ryanair (Ireland). Both Southwest Airlines and Ryanair have been operating profitably , and are useful models for comparison of both the performance and market potential of the Australian low cost airlines. Finally, the study analyses the potential for further development of the low cost airline model in Australia.